(untitled) (Journal of Advanced Research in Social Sciences, 2024)
Education is critical for learning how to communicate with others. Through formal schooling, people learn the language (how to read and write) and interact with others in the same setting. One of the study’s assumptions is that well-educated people communicate well, leading to better jobs and higher income. Another assumption is that communication skills improve with age due to the practicality of employing what has been taught on a daily basis, especially among professionals. An experienced medical doctor, journalist, or educator has enhanced communication skills compared to entrants within the same profession. Also, people with any formal career in the sector have better communication skills than illiterate individuals or those with elementary-level education. In Addition, the chance to apply one’s skills can make a difference in people’s communication skills in varying careers. For these reasons, respondents’ level of education was analyzed with monthly income and work sector. The chi-square test was applied, and it was found that there is a significant relationship between the level of education and monthly income and age group but now work sector. One possible reason for the latter finding is that respondents’ careers and professions were not specified. Despite these findings, there are variables to consider among individuals when assessing their education and communication skills such as their experience and whether they are self-taught.